2020
DOI: 10.21203/rs.3.rs-49933/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rhamnolipid Coating Reduces Microbial Biofilm Formation on Titanium Implants: an in-vitro Study

Abstract: Background: Peri-implant mucositis and peri-implantitis are biofilm-related diseases causing major concern in oral implantology, requiring complex anti-infective procedures or implant removal. Microbial biosurfactants emerged as new of anti-biofilm agents for coating implantable devices preserving biocompatibility. This study aimed to assess the efficacy of rhamnolipid biosurfactant R89 (R89BS) to reduce Staphylococcus aureus and Staphylococcus epidermidis biofilm formation on titanium. Methods: R89BS was phys… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Wood et al proved the rhamnolipid actions against sulfate‐reducing bacteria biofilm since RML are the biochemical basis of biofilm dispersal and antiadhesion 2 . More recently, Tambone and coauthors reported that rhamnolipids decrease biofilm formation on titanium implants 35 . Additionally, various chemical surfactants have biocidal properties 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wood et al proved the rhamnolipid actions against sulfate‐reducing bacteria biofilm since RML are the biochemical basis of biofilm dispersal and antiadhesion 2 . More recently, Tambone and coauthors reported that rhamnolipids decrease biofilm formation on titanium implants 35 . Additionally, various chemical surfactants have biocidal properties 3 .…”
Section: Resultsmentioning
confidence: 99%
“…2 More recently, Tambone and coauthors reported that rhamnolipids decrease biofilm formation on titanium implants. 35 Additionally, various chemical surfactants have biocidal properties. 3 In the present study was shown clearly that the RML (with highlight for mono-RML) was able to prevent biofilm formation more effectively than one of the most popular surfactants used in the oil industry-SDS.…”
Section: Structural Characterization and Polarity Of Rhamnolipidsmentioning
confidence: 99%
“…When exposing single-cell biofilms of P. aeruginosa to rhamnolipids, growth and development were disrupted, and cell viability was reduced (De Rienzo et al ., 2015). Disruptions by rhamnolipids have also been shown for single species biofilms of Staphylococcus aureus (Quinn et al ., 2013; Aleksic et al ., 2017; Tambone et al ., 2021), Bacillus pumilus (Dusane et al ., 2010), and Rhodococcus erythropolis (Schreiberova et al ., 2012). Yet, rhamnolipids are biodegradable in a variety of environments, including under aerobic and anaerobic conditions (Mohan et al ., 2006; Ramos da Silva et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%